INFRASTRUCTURE POLICY IN INDONESIA: NEW DIRECTIONS - McCawley, Peter (Journal of Indonesian Economy and Business, 2010)
Indonesia faces an infrastructure crisis. The infrastructure crisis is part of a broader challenge of mobilising investment capital to support overall development. The basicarguments of this article are as follows. First, long-term development in Indonesia will be held back unless increased amounts of priority infrastructure can be provided. Second, the required infrastructure projects will not be constructed unless bottlenecks holding back the investments can be overcome. Third, bottlenecks appear to fall into two main types: financial and real constraints to growth. Fourth, more emphasis on a commercial approach to the provision of infrastructure in Indonesia which emphasises competitionand responsiveness to stakeholders is needed.Keywords: infrastructure; finance; markets; prices